Assessment of air quality, health status and lung function of workers from selected poultry management systems in Ogun State, Nigeria - Toluwalase Janet Ogunleye; Adewale Matthew Taiwo; Temilade Fola Akinhannmi; Laoye Oluwafemi Oyediran; Toyin Ayodele Arowolo (Elsevier, 2022)
Background/Objectives: This study assessed the air quality, health status and lung function of workers from intensive poultry production systems in selected areas of Ogun State. Methods: Air samples were monitored monthly between November 2017 and April 2018 from six pens in three selected poultry zones of Ogun State. The air pollutants (CO2, CH4, NO2, NH3, H2S, SO2, PM2.5) and the microclimatic parameters around the poultry pens were determined. Copies of structured questionnaires were administered to assess the impacts of air pollutants on the health status of the poultry workers. Lung function parameters [Forced Expiratory Volume in 1 s (FEV1), Forced Vital Capacity (FVC), FEV1/FVC and Peak Expiratory Flow Rate (PEFR)] were measured to assess the pulmonary health of the poultry workers and the control group. Results: The levels of NH3, PM2.5, CO2 and CH4 were higher than the permissible standards while NO2, H2S and SO2 were below the permissible limits of the World Health Organization. Regression analysis between pollutants and microclimatic parameters showed that relative humidity and windspeed had negative effects on PM2.5, NO2, H2S and SO2. FEV1/FVC measured for poultry workers was 86.84 ± 18.32% with 10.0% having obstructive lung function, while the control group had 98.82 ± 1.52% with 100% normal lung function pattern. The predicted PEFR for poultry workers was significantly lower at 61.12 ± 27.85% with 13.3% having severe airway restrictions, while the predicted PEFR for the control group was significantly higher at 88.41 ± 21.76% with no severe airway narrowing. Conclusions: This study established that air quality around the poultry operations affected the workers' health.